Benefit Incidence Analysis of Public Services in Malang Raya - Mujiarti, Astri Oktaviana; Ananda, Candra Fajri; Susilo, Susilo (International Journal of Social and Local Economic Governance, 2016)
BOS and Jamkesmas programs are kind of public services for education and health that have been implemented in Great Malang (Malang City, Batu City, Malang Regency). The purposes of these programs are to give service access for people, especially for the poor and to poverty reduction. The implementation of these programs were not optimal that could cause the poverty rate is still high. The goals of this research is to measure programs effectiveness based on the distribution of benefits with Benefit Incidence Analysis. The measurement of programs effectiveness is done on elementary and junior high school level services from BOS, while the type of Jamkesmas services are outpatient and inpatient.. The measurement of effectiveness was used Susenas data comparation on 2009 and 2013. Based on effectiveness analysis, BOS and Jamkesmas in Great Malang are not effective overall. Malang City have inpatient service that not effective. Batu City have junior high school level and inpatient services that not effective. All of BOS dan Jamkesmas services are not effective in Malang Regency.Keywords: benefit incidence, effective, public service